The Relationship Of Gravidity With The Occurrence Of Preeclampsia In Maternity Women - Sari, Iramaya; Lestari, Aldina (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2018)
World Health Data (WHO) the incidence of preeclampsia ranges from 0.5% - 38.4%. Preeclampsia and eclampsia throughout the World are estimated to cause approximately 14% (50,000-75,000) of maternal deaths each year. The incidence of preeclampsia in the United States alone is approximately 5% of all pregnancies, with a picture of the incidence of 23 cases of preeclampsia found per 1,000 pregnancies each year (Joseph et al, 2008). Meanwhile, in each country, the incidence of preeclampsia varies, but in general, the incidence of preeclampsia in a country is reported to be between 3-10% of all pregnancies. The researcher's goal is to find out the relationship between gravidity and the incidence of preeclampsia at the Bulukumba District Level. Historical cohort research design. The population and sample in this study were patients who experienced preeclampsia 73 and those who did not have preeclampsia 259 people in 20 public Health working areas in Bulukumba District who used cluster sampling techniques after counting the number of samples from each public Health then random sampling would be taken with the measuring instrument used was an observation sheet. Analysis of the data in this study used the Chi-square statistical test. Based on the statistical test obtained P = 0,000 <Î± = 0.005. The conclusion of this study is there is a relationship between Gravidity and the incidence of preeclampsia in maternity mothers. It is recommended that health services need to develop a health education program regarding the incidence of preeclampsia to prevent maternal mortality.